Herpes Simplex Encephalitis Does Interferon Care? - Painho, T (2014)
Introduction and aims: Herpes simplex encephalitis (HSE) is an acute, life-threatening disease, requiring prompt intervention. TLR3-interferon (IFN) axis defects in the antiviral innate immune response against HSV-1 and some genes (TLR3, UNC93B1 and TRAF3) probably play an important role in HSE pathogenesis. Methods: Descriptive study between January 2007 and December 2012 from HSE patients treated with acyclovir (initiated between D2 to D3 of illness) and INF alpha-2b. HSV-1 was detected by PCR from CSF. PBMC and fibroblasts were studied for their IFN responses to TLR3 and virus stimulations. Coding exons of the known HSE-associated genes were sequenced. Results: Six cases, aged between 7 months and 11 years, with seizures and extensive brain injury. Interferon was initiated between D3 and D18. Patient 1 initiated IFN on D18 and stopped 7 days later for bicytopenia. Patient 2 started on D3 and has no sequelae. Patient 4 started on D5 and has persistent right sided hemiparesis. Patient 3, 5 and 6 started on D5, D3 and D7 respectively remain with epilepsy under medical control. Only Patient 1, who started IFN later than D7, has sequelar tetraparesis. None of the other patients have severe neurological deficits. The functional studies were normal, except for patient 1 whose fibroblasts displayed impaired IFN-lambda production after stimulations of poly(I:C), thought to be TLR3-dependent. No mutation was found in the sequenced coding exons of UNC93B1, TLR3 and TRAF3. Conclusions: Although a small sample, our results suggest that IFN therapy should be considered in the treatment of HSE.